Workload, stress, and patient safety in emergency nursing units: An Analytic Cross-Sectional Study - Rasi Rahagia; Zusana A. Sasarari; Yunita Kristina; Darmi Arda; Chanchal Kurup (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Emergency departments represent high-risk clinical environments where workforce strain may compromise patient safety. The World Health Organization reports a global shortage of health workers exceeding 10 million, disproportionately affecting acute care settings. According to the Global Burden of Disease study, non-communicable diseases and injury-related conditions continue to drive emergency service utilization worldwide. In many middle-income countries, increasing patient volume and limited staffing contribute to excessive nurse workload and occupational stress, which are recognized determinants of adverse events and reduced safety compliance. To examine the association between workload, occupational stress, and patient safety practices among nurses working in emergency units. Research Methodology: An analytic cross-sectional study was conducted among 80 emergency nurses in a tertiary hospital. Total sampling was applied. Data were collected using validated self-administered questionnaires measuring workload, occupational stress, and patient safety practices. Bivariate analysis was performed using Chi-square tests, followed by multivariate logistic regression to estimate adjusted odds ratios (AOR) with 95% confidence intervals (CI). Statistical significance was set at α = 0.05. Results: High workload was significantly associated with inadequate patient safety practice (AOR = 3.05; 95% CI: 1.14–8.15; p = 0.026). High occupational stress also independently predicted inadequate safety practice (AOR = 2.47; 95% CI: 1.01–6.05; p = 0.048). The final model explained 31% of the variance in patient safety outcomes. Conclusion: Excessive workload and occupational stress are significant determinants of patient safety performance in emergency nursing units. Workforce regulation, staffing optimization, and stress mitigation strategies should be integrated into hospital quality improvement and public health workforce policies.